Golden Adornments of Volga Bolgaria and the Bolgar Ulus of the Golden Horde: comparative analysis experience - Rudenko Konstantin A. (Поволжская археология, 2018)
The paper considers gold adornments dating back to the 10th –14th centuries and associated with Volga Bolgaria and the Bolgar Ulus of the Golden Horde. The author determined that the range of products was stable during the period under study. The Bolgars wore signet rings, bracelets, pendants, temple rings and earrings. In the Golden Horde period, gold was used to produce belt details and clothing decorations. However, the design and technology of crafting the artefacts were different. The Bolgars developed Golden adornments during the 11th –12th century on the basis of local traditions with the application of technologies practices by the jewellers of the Middle East (Syria, Egypt), and perhaps with their direct participation. A portion of golden jewellery was imported to Bolgaria in the 12th – early 13th centuries from Oriental countries. In the Golden Horde period, golden adornments were an indicator of the social status of the wearer. Most of them were imported, and other artefacts were produced in accordance with the jewellery traditions of the Golden Horde.